Indonesia: Epidemiological Profiles of Early Childhood Caries - Amalia, Rosa; Chairunisa, Fania; Alfian, M. Fahmi; Supartinah, Al (Frontiers in Public Health, 2019)
Indonesia is one of the developing countries with a rapidly growing economy in Southeast Asia. The Indonesia government has succeeded in achieving national health development targets and has invested heavily in public health. However, like anywhere else in the world, result of previous study on early childhood caries (ECC) in pre-school children showed a high prevalence and severity. Regarding these interests, the purpose of this study is to provide a comprehensive review seen from the epidemiological aspects of ECC obtained from national basic health survey between 2007-2018 which complemented by data from the publications on ECC in Indonesia. Aspects of access, utilization and description of dental health workers in Indonesia obtained from the Indonesian Health Profile Report is also explored.